Communication quality between the medical team and the head coach/manager is associated with injury burden and player availability in elite football clubs - Ekstrand, J.; Lundqvist, D.; Davison, M.; D´Hooghe, M.; Pensgaard, A. M. (British Journal of Sports Medicine, 2019)
Objectives: We investigated medical staff interpretations and descriptions of internal communication quality in elite football teams to determine whether internal communication was correlated with injuries and/or player availability at training and matches. Methods: Medical staff from 36 elite football clubs across 17 European countries produced 77 reports at four postseason meetings to provide their perceptions of internal communications in their teams. They also recorded data on individual players` exposure to football and time-loss injuries. Results: The injury burden and incidence of severe injuries were significantly higher in teams with low quality of communication between the head coach/manager and the medical team (scores of 1-2 on a 5-point Likert scale) compared with teams with moderate or high-quality scores (scores of 3-5; p=0.008 for both). Teams with low scores had 4%-5% lower training attendance (76% vs 83%, p=0.001) and less availability at matches (82% vs 88%, p=0.004) compared with teams with moderate or high communication quality scores. Conclusions: The quality of internal communication within a team was correlated with injury rates, training attendance and match availability. Abstract from author